E-Charity Application to Help Poverty in Kuala Lumpur: Fundle - Fareez Bin Jasmi, Mohamad; Kumar Appadurai, Naresh (International Journal of Psychosocial Rehabilitation, 2019)
The Malaysian economy has seen a significant growth ever since the independent in 1957 and has excellently changed the country from poor into a middle-developing nation. Therefore, this success has helped the country to combat poverty issues effectively throughout the year. Despite this success, there is still an existing group of poverty in Kuala Lumpur that are struggling themselves to survive. This paper aims to analyse and assess the characteristics of poverty group and donators in Kuala Lumpur, other current problems that relate to the poverty issue, charity organizations status in Malaysia and the proposed solution to reduce the poverty rate. Also, to help the hidden poverty group in Kuala Lumpur by encouraging people to donate more to charity houses. This paper explores a mobile based technology solution to perform donations more effectively using solutions like GPS and Cloud infrastructure in order to bridge donors and the needy in a more efficient manner